The Effect of Family-based Intervention on Overweight/ Obesity in Children: Meta Analysis - Mario Febrianus Helan Sani; Yulia Lanti Retno Dewi; Bhisma Murti (Journal of Health Promotion and Behavior, 2021)
Background: Childhood overweight and obesity is one of the most serious public health challenges of the 21st century. Overweight and obesity are one side of the double burden of malnutrition because more than 1.9 billion people are overweight and of that number more than 650 million are obese. Meanwhile, for children aged 5-19 years, more than 340 million children are overweight and obese. One category of intervention to prevent overweight / obesity in children who have developed rapidly in recent years is family-based intervention. This study aims to estimate the magnitude of the effect of family-based intervention on overweight / obesity based on the results of a number of previous studies.Subjects and Method: This was a systematic study and meta-analysis carried out by following the PRISMA flow diagram. The process of searching for articles through a journal database which includes: Google Scholar, PubMed, ScienceDirect and SpingerLink by selecting articles published in 2005-2020. Keywords used include: “family-based intervention” OR “family-based program” OR “family-based treatment” OR “family-based” OR “home-based intervention” OR “household based intervention” AND “children overweight OR "childhood overwight" AND "pediatric obesity" OR "children obesity" OR "children obese" OR "childhood obesity" OR "childhood obese" AND RCT OR "randomized controlled trial" OR "cluster-randomized controlled trial". The inclusion criteria were a full paper article with a randomized controlled trial (RCT) study design, the article used English, the study subjects were overweight / obese children (aged 5-19 years) and the intervention given was family-based intervention. Articles that meet the requirements are analyzed using the Review Manger 5.3 application.Results: A total of 11 articles reviewed in this meta-analysis study came from Malaysia, the United States, Australia, England, Spain, Denmark and Sweden. Meta-analysis of 11 articles with a randomized controlled trial (RCT) study design showed that family-based intervention had an effect on reducing children's body mass index but it was not statistically significant (Standarized Mean Difference= -0.46; 95% CI -1.05 to 0.13 p= 0.130).Conclusion: Family-based intervention reduces body mass index for overweight / obese children.Keywords: family-based intervention, overweight, obesity, children, meta analysisCorrespondence: Mario Febrianus Helan Sani. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Jawa Tengah. Email: rhyansani@gmail.com. Mobile: 081326608972.Journal of Health Promotion and Behavior (2021), 06(01): 45-56https://doi.org/10.26911/thejhpb.2021.06.01.05